Scaling morphosemantic transparency/opacity: A corpus-linguistic and acquisitionist study of German diminutives - Ransmayr, Jutta; Schwaiger, Sonja; Korecky-Kröll, Katharina; Sommer-Lolei, Sabine; Dressler, Wolfgang U. (Yearbook of the Poznan Linguistic Meeting, 2017)
The judicious use of electronic corpora allows new possibilities in the study of word formation. In contrast to the usual way of contrasting morphosemantic transparency (or compositionality) and morphosemantic opacity (or non-compositionality) in a dichotomous way, we present a ten-step scale from maximum transparency to total opacity, exemplified with the common German diminutive suffixation in -chen and Austro-Bavarian -erl. Our corpus-linguistic investigation allows new insights into problems of distribution of type and token frequency according to degrees of morphosemantic transparency/opacity and of the two rivalling diminutive formations. An analysis of diminutive acquisition is added as external evidence for or against previous claims. Acquisition data come from three longitudinal corpora and from 24 children of a transversal quasi-longitudinal study. Here the order of acquisition of diminutives according to the ten-step scale of morphosemantic transparency/opacity and to adult type and token frequency will be presented and the relation between morphosemantic and morphopragmatic meaning will be discussed.